Synthesising Stanislavsky into the African aesthetics of contemporary South Africa - Johnson, Bertina (University of the Witwatersrand, Johannesburg, 2024)
The purpose of this study is centred upon an investigation into the possibility of synthesising African aesthetics, as present in modern-day South African theatre, with the methods and philosophy of Stanislavsky in both the training of actors and in theatre performance, reframing the continuum whereby the two methods seem to exist. Presently, the two are often regarded as separate categories, one for realism, the other for more traditional African-based performance and South African presentational theatre. This research entails an examination into the nature of African aesthetics, which includes both the values and ideas surrounding an African worldview, as expressed in literature and in theatre, as well as the significance of post-colonial thought in contemporary South Africa, such as the theories of Afrocentricity and black consciousness, alongside the deciphering of how these approaches and influences are relevant to the creating of South African theatre. The issues surrounding Afrocentricity in training and in theatre are examined in terms of the codes of interculturalism, post-colonial theatre, syncretic theatre and cultural imperialism. This has included theories that apply to the nature of sacred theatre and the polysemic nature of contemporary performances of traditional theatre. Pertinent to and contained within this study is the question of the methods, philosophy and worldview of Stanislavsky, as well as the influence of his position as the creator of what is known as the System. In the process of further defining how and if synthesis is possible, the concepts and methods of his work are examined about the meanings underlying his terms, particularly in the light of more accurate and detailed recent translations, which more directly relate to the spiritual nature of his concepts. The significance that much of Stanislavsky’s work is based on spiritual concepts has been referenced to the spirituality found in African aesthetics and worldview, with a specific regard to the notion of an animated world that contains a force field of energy, which I have named an animated theatre in contrast to the psychological interiority found in much of Western actor training and performance. I have argued that acknowledgment of the articulation of the soul and the spirit in Stanislavsky as vital to the actor’s work was often 8 eradicated or ignored and the subsequent re-evaluation of translations of his written work from Russian to English has opened numerous possibilities in the training of actors and in performance, especially in the consideration of his concepts of experiencing, the creative state, communion, aktivnost and resonance with the audience in relation to the African world view. Included in the research is an ethnographic study of the work I have done as a teacher and director in South Africa, considered along with the creative research, as a way of comparing my Western-based training in both the USA and Europe to the discoveries I have made while practicing theatre in South Africa. Examining the theories of integration and synthesis, of Afrocentricity, the African world view and the underlying philosophy of Stanislavsky’s methods through the creative research, with the exploration of methods of both African performance and Stanislavsky, contributes to the process of evolving effective actor training and dynamic South African theatre. It has led to the discovery of what I have labelled as ‘an animated theatre’, which conveys the intersection between African aesthetics and the work of Stanislavsky, through tracing the innovative possibilities of a conscious synthesis in both the creation of theatre and in the training of actors. Acting terms, such as ‘the creative state’, which are taken for granted, thus take on new meaning when the concept and theory of the spiritual state, as meant by Stanislavsky, and how it influences expression, is not eradicated but acknowledged. Through working in the specifics of locality, for a comprehension of varied cultures, and within the paradigm of African aesthetics and Stanislavsky, an analysis of the relatedness of values held in each system, integration and synthesis becomes possible. The notion of an acting system driven by the energetic concepts of both African aesthetics and Stanislavsky, which correlate to the neuroscience of the linkage of mind, body and emotions, puts forward new theories for exploration in terms of physical expression and the inner and outer continuum of the actor’s expression and indicates opportunities for reevaluating the training of actors. My aim in this study has been to expand the knowledge of this evident synthesis, thereby contributing to the future possibilities in the creation of performance and in the training of the talented young actors so present in Southern African theatre.
A research report Submitted in fulfillment of the requirements for a Doctor of Philosophy (PhD) In the Department of Theatre and Performance, In the Faculty of Humanities , School of Arts, University of the Witwatersrand, Johannesburg, 2024
Keywords: synthesising African aesthetics; philosophy of Stanislavsky; actors; theatre performance; SDG-17: Partnerships for the goals